2011
DOI: 10.1111/j.1462-5822.2010.01564.x
|View full text |Cite
|
Sign up to set email alerts
|

Exit of intracellular Porphyromonas gingivalis from gingival epithelial cells is mediated by endocytic recycling pathway

Abstract: SummaryGingival epithelial cells function as an innate host defence system to prevent intrusion by periodontal bacteria. Nevertheless, Porphyromonas gingivalis, the most well-known periodontal pathogen, can enter gingival epithelial cells and pass through the epithelial barrier into deeper tissues. However, it is poorly understood how this pathogen exits from infected cells for further transcellular spreading. The present study was performed to elucidate the cellular machinery exploited by P. gingivalis to exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 56 publications
3
61
0
2
Order By: Relevance
“…An exocytosis-type process termed "vomocytosis" has been implicated in the exit of fungal pathogens from macrophages (33,34), although this process is likely distinct from the polarized exocytosis used to escape from epithelial cells. Whereas exocytosis has been shown to contribute to bacterial pathogen exit in mammalian tissue culture systems of epithelial cells (35), multiple modes of exit have been proposed for the same pathogen, and the in vivo significance and contribution of exocytosis to disease transmission has not been clear. In contrast to the C. elegans intestine, the mammalian intestine regularly renews and sheds epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…An exocytosis-type process termed "vomocytosis" has been implicated in the exit of fungal pathogens from macrophages (33,34), although this process is likely distinct from the polarized exocytosis used to escape from epithelial cells. Whereas exocytosis has been shown to contribute to bacterial pathogen exit in mammalian tissue culture systems of epithelial cells (35), multiple modes of exit have been proposed for the same pathogen, and the in vivo significance and contribution of exocytosis to disease transmission has not been clear. In contrast to the C. elegans intestine, the mammalian intestine regularly renews and sheds epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…The direct or indirect effects of circulating bacteria, inflammatory mediators and/or immune complexes from infected/inflamed periodontal tissues on other body sites are some of the main mechanisms that contribute to systemic inflammation [17]. Oral bacteria can enter the circulation and cause bacteraemia by actively crossing the periodontal epithelium [1820], or by being inoculated through mechanical procedures, including periodontal debridement, flossing and brushing [21,22]. Periodontal pathogens, such as Aggregatibacter actinomycetemcomitans, Treponema denticola and Porphyromonas gingivalis are also capable of invading endothelial cells [2327], and they have been detected in atherosclerotic plaques, heart valves, aortic aneurysms, carotid and coronary vessels [2833].…”
Section: Introductionmentioning
confidence: 99%
“…P. gingivalis may persist in these autophagosome vacuoles, and inflammation and cell damage can result from accumulations of high loads of intracellular organisms. In our study, wortmannin (autophagy inhibitor) was effective to reduce the number of intracellular bacteria, 6 indicating the possibility that autophagy allows intracellular P. gingivalis to survive. However, the role of autophagy in survival of intracellular P. gingivalis has not been well defined and is currently being examined in our laboratory.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 93%
“…2). 6 P. gingivalis was internalized with early endosomes positive for the FYVE domain of EEA1 (an early endosome marker) and transferrin receptor, and about half of the intracellular bacteria were found to be sorted to lytic compartments, including autolysosomes and late endosomes/lysosomes, while a considerable number of the remaining organisms were sorted to Rab11-and RalA-positive recycling endosomes, followed by the bacterial exit. Inhibition experiments revealed that bacterial exit is dependent on actin polymerization, lipid rafts and microtubule assembly, while dominant negative forms and RNAi-knockdown of Rab11, RalA and exocyst complex subunits (Sec5, Sec6 and Exo84) significantly disturbed the exit of P. gingivalis.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
See 1 more Smart Citation